Immune Checkpoint Inhibitors in Real‐World Treatment of Older Adults with Non–Small Cell Lung Cancer. Issue 5 (30th January 2019) - Muchnik, Eugene; Loh, Kah Poh; Strawderman, Myla; Magnuson, Allison; Mohile, Supriya G.; Estrah, Vered; Maggiore, Ronald J.
Abstract : OBJECTIVE: To evaluate the efficacy and toxicity of immune checkpoint inhibitors (ICIs) in older patients with advanced non–small cell lung cancer (NSCLC) seen in routine clinical practice. DESIGN: Retrospective study. SETTING: Single academic institution and its affiliated centers. PARTICIPANTS: Patients 70 years or older with advanced‐stage NSCLC seen between April 1, 2015, and April 1, 2017, and treated with ICIs. MEASUREMENTS: Efficacy data included overall survival (OS) and time to treatment failure (TTF), stratified by age, comorbidities (Charlson Comorbidity Index [CCI]), and Eastern Cooperative Oncology Group Performance Status (ECOG PS), and estimated using the Kaplan‐Meier method and log‐rank test. Toxicity data included immune‐related adverse events (irAEs), need for glucocorticoids, and hospitalization. The associations of toxicity with age, CCI, and ECOG PS were evaluated using the exact χ 2 test or Fisher exact test. RESULTS: We included 75 patients (median age: 74 y; range, 70‐92 y); 53% had a CCI of 3 or higher; 49% had ECOG PS of 2 or higher. Median OS for the whole cohort was 8.2 months (ECOG PS 0‐1 vs ≥2: 13.7 vs 3.8 mo; p < .01). Median TTF was 4.2 months (ECOG PS 0‐1 vs ≥2: 5.6 vs 2.0 mo; p = .02). Overall, 37% of patients experienced irAE of any grade (a total of 37 events); 8% were grade 3 or higher (no ICI‐related deaths). Of those who discontinued ICIs (N = 64), 15% were due to irAEs. Of those who experienced irAEs, 64% required glucocorticoids. Hospitalizations during ICI treatment occurred in 72%. Toxicity generally did not differ by age, CCI, or ECOG PS. CONCLUSIONS: Outcomes in our cohort were driven by ECOG PS rather than chronological age or comorbidities. The relatively high rates of ICI discontinuation, use of glucocorticoids, and hospitalization during ICI treatment in our study highlight the vulnerability of older adults with advanced NSCLC even in the immunotherapy era. J Am Geriatr Soc 67:905–912, 2019.